Students at Saarland University dental school—A survey on their background and curriculum perception. (27th November 2020) - Meyer, Birgit; Karl, Matthias; Luft, Torsten; Koch, Simon; Grobecker‐Karl, Tanja; Steiner, Constanze
Abstract: Introduction: With the aim of optimising dental education without overburdening students, new legislation restructuring the undergraduate dental curriculum in German is under way. The goal of this study was to survey the current situation of dental students at one specific university with respect to their socio‐economic background, admission to dental school, curriculum perception and work‐life balance. Materials and methods: An online questionnaire was presented to all undergraduate students enrolled at Saarland University who had at least completed the first preclinical practical course in dentistry. Results: A response rate of 85% was reached with two‐thirds of the student body being females. The profession of 40% of students' parents either was physicians or dentist. Students reported a slight reduction in time spent for leisure activities during their studies, however, with sports activities hardly being affected. With respect to a proper work‐life balance, almost 50% of respondents considered their clinical workload as being too high. Students did not express a clear opinion regarding curriculum structure, whilst the content mostly satisfied their expectations (59%). The majority (71%) of students considered their preclinical training as being demanding whilst less than 3% fully agreed that preclinical training provided an optimal background for patient treatment. The learning modules in the first clinical semester were considered as being adequate by 56% of students. Examinations during courses were seen as properly reflecting the students' knowledge by 79% of students. Discussion: The status quo of German dental students is characterised by a high workload affecting the students' work‐life balance and by a transition between preclinical and clinical education which only about half the student body perceives as being adequate. Patient‐based examinations obviously are not considered as being problematic.